Hip bone marrow edema presenting as low back pain: a case report. (2nd January 2020) - Mourad, Firas; Maselli, Filippo; Cataldi, Fabio; Pennella, Denis; Fernández-De-Las-Peñas, César; Dunning, James
ABSTRACT: Background : Nonspecific low back pain (LBP) is frequently managed by physiotherapists. However, physiotherapists in a direct access setting may encounter patients with serious medical conditions, such as Bone Marrow Edema Syndrome (BMES) of the hip with symptoms mimicking LBP. To our knowledge, this is the first case to describe hip BMES presenting as LBP. Diagnosis was based on the patient's symptoms in conjunction with magnetic resonance imaging (MRI). In order to avoid misdiagnosing the patient, primary care clinicians should be aware that BMES can mimic nonspecific LBP. Objective : To present a rare clinical presentation of BMES of the hip mimicking nonspecific LBP. To the best of the author's knowledge, this is the first case to describe hip BMES presenting as mechanical nonspecific LBP. Case presentation : This case report describes the history, examination findings, and clinical reasoning used for a patient with LBP as a chief complaint. Furthermore, the clinical presentation (i.e. pain location and its changes related to load) and the symptoms behavior (i.e. immediate symptoms decrease after few hip treatment sessions and quick worsening of the hip pain related to loading activities) after two treatment sessions increased the suspicion of an underlying medical condition of the hip joint and lead to the decision for additional evaluation. A MRI showed a serious hip BMES. Conclusions : This case report highlights the importance of including a comprehensive and continuous differential diagnostic process throughout the treatment period, looking for those risk factors (i.e. red flags) that warrant further investigation and referral to the appropriate physician. Physiotherapy diagnosis should include clinical reasoning, clinical presentation, and symptom behavior in addition to appropriate referral for medical assessment and diagnostic imaging when appropriate. Physiotherapists working within a direct access environment have the competence and responsibility to participate with other health professionals in the differential diagnose process especially for patients presenting with serious pathology mimicking musculoskeletal disorders.